Phytochemical-Mediated Modulation of Doramectin Pharmacology in Sheep: Exploring the Cinnamaldehyde–Pink Grapefruit Combination - Miró, María Victoria (2025)
Phytotherapy represents a promising field for developing new therapeutic strategies, either by acting as antiparasitic agents themselves or by enhancing the efficacy of synthetic drugs. The present study evaluated the in vivo pharmacokinetic and pharmacodynamic interactions following the administration of doramectin, either alone or in combination with cinnamaldehyde and pink grapefruit essential oil (CNM–PGF). Additionally, ex vivo P-glycoprotein-mediated interactions were assessed at the intestinal level. Higher efficacy against Haemonchus contortus was observed with the combined treatment of doramectin plus phytochemicals or loperamide. Although phytochemicals and loperamide reduced the ex vivo efflux of rhodamine 123, no pharmacokinetic interactions were detected in vivo. The enhanced efficacy is most likely attributable to localized drug–drug interactions and increased drug availability at the parasite interface. Based on the results obtained, the best treatment would be the combination of DRM with phytochemicals such as CNM–PGF and loperamide. However, a pharmaceutical formulation that allows sustained in vivo interaction between these compounds is needed.